One Team–Patient, Family, and Health Care Providers: An Interprofessional Education Activity Providing Collaborative and Palliative Care - Prelock, Patricia A.; Melvin, Christina; Lemieux, Nancy; Melekis, Kelly; Velleman, Shelley; Favro, Mary Alice (Seminars in Speech and Language, 2017)
The article explains an approach to building interprofessional education (IPE) and interprofessional practice opportunities as well as content in palliative/hospice care within undergraduate and graduate curricula for six health disciplines, including speech-language pathology. Graduate students from nursing, medicine, communication sciences, and disorders, physical therapy, social work and nutrition, as well as undergraduate nursing students participated in one of four IPE training sessions using six videotaped simulation scenes portraying the progression of amyotrophic lateral sclerosis. Learning objectives included (1) engaging in effective interprofessional communication and teamwork, (2) discussing therapeutic patient/family communication, (3) employing supportive holistic care with patients and families at end of life, and (4) relating the patient's physiological assessment findings to the dying process. Students discussed the role of the interprofessional team in end-of-life care and were coached on ways to apply interprofessional communication, a key interprofessional education competency, using patient- and family-centered care principles. Results revealed strong positive agreement among the disciplines regarding the value of the learning opportunities provided during this IPE simulation activity.
Keywords: Interprofessional education; palliative care; collaboration